The consumer loss of the minimum duration for mobile telephone calls - Grzybowski, L.; Pereira, P. (Telecommunication Policy, 2009)
This article estimates price elasticities of demand for the duration of mobile telephone calls for Portugal, as well as the monetary loss per consumer of the existence of a minimum duration of calls. The demand for the duration of calls is estimated using a Tobit model for panel data with individual random effects. The elasticity of demand is found to be small and to vary across firms. At current prices, the average duration of calls ranges between 101 and 109 s, while the estimated average length of calls without minimum duration ranges between 63 and 66 s. Hence, the existence of a minimum duration for calls results in a monetary loss of 35-40% of the average invoice.